Basic nursing : essentials for practice - Potter, Patricia A.; Perry, Anne Griffin (Singapore : Elsevier, 2007)
This user-friendly textbokk provides you with complete coverage of the essential nursing principles, concepts, and skills that are the foundation of a solid nursing education.
Unit I: Concepts in heealth care -- Unit II: Processes in nursing care -- Unit III: Principles for nursing practice -- Unit IV: Principles for caring -- Unit V: Caring for patients' basic human needs -- Unit VI: Caring for patients' special needs
Includes index.
Keywords: EDUCATION, NURSING